PULSED ELECTROPOLYMERIZATION OF POLYANILINE AS A COUNTER ELECTRODE IN DYE-SENSITIZED SOLAR CELLS (DSSC) - Dini Lestari, Fawziah
In this day, solar cells have developed up to three generations. Dye-sensitized solar cells (DSSC) is one of the third-generation solar cells based on semiconductor nanoparticles with the basic principle of photoelectrochemical phenomena in producing electrical energy. One of the important components in the DSSC device is the counter electrode. DSSC requires a counter electrode that has a high electrocatalytic activity to reduce ions to ions in the process of regeneration of the redox pair electrolyte . One material often used as a counter electrode is conductive polyaniline conductive polymer (PANI). As a counter electrode material, PANI has many advantages, including simple synthesis steps, low production costs, high electrocatalytic activity, relatively high electrical conductivity, and being environmentally friendly. In this study, PANI was synthesized using the pulsed electropolymerization method. The method produces PANI with controlled uniformity and particle size, short reaction time, simple synthesis procedure, and does not require an oxidizer. The variation in parameters carried out in the synthesis using the pulsed electropolymerization method in this study is the duty variation, namely the ratio of the pulse width time to the distance between pulses in the range of 10 to 70%. The synthesized PANI samples were then structurally characterized using Raman spectroscopy and Fourier Transform Infrared-Attenuated Total Reflectance (FTIR-ATR). Optical characterization was carried out by measuring UV-Vis Diffuse Reflectance Spectroscopy (UV-Vis DRS). Morphological characterization was carried out using Field Emission Scanning Electron Microscopy (FESEM). In addition, energy conversion efficiency performance tests were also carried out on the DSSC device using the Keithley 2400 device and Solar Simulator. The results of Raman characterization indicate that the PANI produced in the pulsed electropolymerization process is PANI ES which is characterized by the presence of the main peaks of PANI ES at the Raman shift of 1618 is a stretching vibration in the benzenoid ring,1595 is the stretching vibration of in the kuinonoid ring, 1457 is the stretching vibration of in emeraldine base (imine site), 1380 is stretching vibration of in the polaronic state (polaron), 1220 is the stretching vibration of in emeraldine (amine site), 1183 is bending vibration of in leucoemeraldine, 1160 is bending vibration of in emeraldine. The results of FTIR-ATR characterization show that the typical peaks of PANI at a wave number of 1555 is vibration on the kuinonoid ring, 1458 is the vibrations on the benzenoid ring, 1286 is vibration from secondary aromatic amine, 1234 is stretching vibration of polaronic state (polaron), 1115 is the vibration of in the kuinonoid ring, 875 is bending vibration of out of the plane of the ring, 790 is the vibrational deformation out of the plane of the kuinonoid ring. The results of the UV-Vis DRS characterization show that the absorption peak around the wavelength of 285 nm is the absorption of ions. The FESEM characterization results show that the synthesized PANI morphology was rods with a rough surface. This rough PANI surface is then used to reduce ions to ions in the process of regeneration of the redox pair electrolyte . The results of energy conversion efficiency performance testing on DSSC devices resulted in an efficiency value of 0,12; 0,72; 1,83; 1,85; 2,41; 2,31; dan 1,83%. Based on the results of characterization and testing that have been carried out, the optimum duty for synthesizing PANI by pulsed electropolymerization is 50%, which is characterized by the highest DSSC cell performance, which is 2,41%.